Diet composition of bigeye tuna (Thunnus obesus) and yellowfin tuna (Thunnus albacares) caught on aggregated schools in the western equatorial Atlantic Ocean - Silva, Guelson Batista da; Hazin, Humberto Gomes; Vieira Hazin, Fabio Hissa; Vaske-Jr, Teodoro [UNESP] (Wiley-Blackwell, 2019)
The present study aims to characterize and compare the diet of bigeye and yellowfin tunas caught on aggregated schools in the western equatorial Atlantic Ocean. The samples were collected from January 2011 to June 2016. The tunas were measured on board and the stomachs were removed after evisceration. The stomachs were analyzed regarding their Index of Fullness and the importance of each prey in the diet was estimated by the Index of Relative Importance (IRI). The diet overlap was assessed by the Morisita-Horn's Index, Non-Metric Multidimensional Scale (NMDS), and Analysis of Similarity (ANOSIM). The feeding strategy was determined by the Costello's Diagram. The 195 bigeye and 212 yellowfin tunas ranged in fork length from 51 to 137 cm and 43 to 174 cm, respectively. The diet of bigeye tuna was composed of 10 families of fish, three cephalopod families, and four crustacean orders. The diet of yellowfin tuna was composed of 11 families of fish, three cephalopod families, and three crustacean orders. The yellowfin tuna seems to feed upon more abundant prey species near the surface like flying fish, which have the concentration enhanced by the light attractors on the boat, and occasionally on other prey from deeper habitats like lanternfish, squids, and pomfret. Bigeye tuna feed mainly at prey that commonly occurs in deeper habitats like squids, drift fish, lanternfish, and pomfret.
Keywords: feeding habits; Fish Aggregated Devices (FADs); food item; prey size; stomach content